Analysis of the perception of High School students about the Chemistry learning process (Research, Society and Development, 2021)
This research aimed to analyze the perceptions of students of the third year of high school in cities of the swamp of Paraíba about the learning process in the discipline of chemistry. Therefore, it is understood that learning chemistry is fundamental for the understanding of various phenomena and transformations that occur in our daily lives, enabling the relationship between theory and practice of various chemical concepts. Thus, for this type of learning to occur, it is necessary that teaching enables the student to go beyond the memorization of content, as the teaching and learning process must take place within a constructive perspective. For data construction, we carried out a quantitative, interpretive and descriptive study, with data quantification. Data collection took place through the application of a questionnaire composed of objective questions. The research was carried out in four municipalities located in the swamp of Paraíba, being developed in state schools in the municipalities of Arara, Areia, Bananeiras and Solânea. The results achieved point to the need for methodological and didactic changes that can increasingly improve the learning of chemical concepts. In addition, we highlight the need to use different teaching approaches, such as the use of contextualization and experimentation as fundamental strategies for the best learning of students. It is understood that the supported teaching, from these perspectives allows a greater motivation of students to learn Chemistry, because in addition to exploring content related to their daily lives, they will become citizens capable of developing a critical and reflective sense.